Kampung Ekopolis: Edukasi dan Aksi Nyata Pengelolaan Sampah Terpadu oleh Komunitas Pemuda Kabupaten Pandeglang - Nandang Kosim; Desyi Rosita; Ahsan Irodat; Fia Nuraeni (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2025)
ECOPOLIS VILLAGE: EDUCATION AND REAL ACTION ON INTEGRATED WASTE MANAGEMENT BY THE PANDEGLANG REGENCY YOUTH COMMUNITY. The increase in waste volume without a proper management system has become a serious problem in Pandeglang Regency. The lack of education and active participation of the community, especially young people, in waste management has led to waste accumulation and potential environmental pollution. The “Kampung Ekopolis” community service program aims to empower youth communities in implementing a community-based integrated waste management model. The program implementation method consists of three main stages: (1) Education and Socialization, through counseling on waste sorting, the impact of plastic waste, and the 3R concept (Reduce, Reuse, Recycle); (2) Concrete Action, through the establishment of a waste bank unit, training in ecobrick making, and organic waste composting; and (3) Simple Infrastructure Development, in the form of a sorted waste collection point. The results of this program show an 80% increase in the youth community's knowledge and awareness of waste management. In concrete terms, a waste bank has been established, which has collected 150 kg of inorganic waste in one month, as well as producing ecobricks and compost that can be reused by the community. The Ekopolis Village program proves that youth communities can be effective agents of change in creating a clean, healthy, and sustainable environment. The sustainability of the program is ensured through partnerships with relevant agencies and transparent financial management of the waste bank by local youth.